Extracorporeal blood purification is associated with improvement in biochemical and clinical variables in the critically‐ill COVID‐19 patients. Issue 2 (16th September 2021) - Premužić, Vedran; Babel, Jakša; Gardijan, Danilo; Lapić, Ivana; Gabelica, Rajka; Ostojić, Zvonimir; Lozić, Marin; Pavliša, Gordana; Hrabak, Maja; Knežević, Josip; Rogić, Dunja; Mihaljević, Slobodan
Abstract: This study tried to investigate the impact of oXiris filter on both clinical and laboratory parameters in critically‐ill COVID‐19 intensive care unit (ICU) patients receiving extracorporeal blood purification and the clinical setting for the initiation of therapy. A consecutive sample of 15 ICU patients with COVID‐19 was treated with oXiris membrane for blood purification or for support of renal function due to acute kidney injury. We have included 19 non treated ICU COVID‐19 patients as a control group. Two chest x‐rays were analyzed for determining the chest x‐ray severity score. We have found a significant decrease of SOFA score, respiratory status improved and the chest x‐ray severity score was significantly decreased after 72 h of treatment. IL‐6 significantly decreased after 72 h of treatment while other inflammatory markers did not. Respiratory status in the control group worsened as well as increase in SOFA score and chest x‐ray severity score. Survived patients have shorter time from the onset of symptoms before starting with extracorporeal blood purification treatment and shorter time on vasoactive therapy and invasive respiratory support than deceased patients. Critically‐ill patients with COVID‐19 treated with extracorporeal blood purification survived significantly longer than other ICU COVID‐19 patients. Treatment with oXiris membrane provides significant reduction of IL‐6, leads to improvement in respiratory status, chest x‐ray severity score, and reduction of SOFA score severity. Our results can suggest that ICU COVID‐19 patients in an early course of a disease could be potentially a target group for earlier initiation of extracorporeal blood purification.